Physical Activity-Related Health Competence: From the Development of a Multidimensional Assessment Instrument to Population-Specific Model Results - Carl, Johannes (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)
In Germany, even though the health aspect was still been doubted as an integral element of sport science until the early 1990s (see, for example, the instrumentalization debate), questions related to health have gained increasing importance and popularity in recent decades. On a global level, health-related physical activity promotion can be divided into individual approaches, on the one hand, and environmental-structural approaches, on the other. The physical activity-related health competence (PAHCO) model, which is identifiable as an individual approach, assumes that people require three central sub-competences to lead a healthy, physically active lifestyle: movement competence, control competence, and self-regulation competence. These sub-competences are, in turn, the result of the coupling of basic elements. Manuscript A, which constitutes the first conceptual study of its kind on the international level, focused on elaborating the theoretical link between the sub-competence level and the level of basic elements by describing how the integration of skills, knowledge, and attitudes may vary across situations and individuals. In this context, a theoretical article from the educational-vocational sciences served as a blueprint to introduce the ideas of low-road, high-road, and transformative integration (Baartman & DeBruijn, 2011). The integrative ideas were also used to highlight the interlocking of exercise, learning, and experiencing necessary for interventions. We further located PAHCO at the interface between health literacy (Sørensen et al., 2012) and physical literacy (Edwards et al., 2017) research and integrated it into the more comprehensive capability approach (Ruger, 2010; Sen, 2005). Subsequently, theory of science considerations stressed that the PAHCO model contains important interdisciplinary ideas and, thus, merits the status of a “middle-range theory” (Merton, 1968; Willimczik, 2001) of comparably broad application scope. This characteristic, in turn, allows researchers to set up a research program across different populations. According to Herrmann (1976, 1994), such a research program can be classified as quasi-paradigmatic. Owing to beneficial conditions at the chair Physical Activity and Health of the Friedrich-Alexander University Erlangen-Nürnberg, this doctoral dissertation was able to realize such a research program through (a) the development of a multidimensional assessment instrument for PAHCO and (b) the accumulation of population-specific model results. Building on a published three-factor measurement model for PAHCO (Sudeck & Pfeifer, 2016), the author of this doctoral thesis performed a stepwise extension of measurement models in four different populations. Manuscript B reports the findings of a five-factor measurement model applied to a sample of 341 rehabilitants with chronic obstructive pulmonary disease (COPD) and of an eight-factor measurement model applied to a sample of 745 apprentices in nursing care and automotive mechatronics. More specifically, this study presents results regarding reliability, factorial validity, discriminant validity, and criterion validity. Using data from 475 individuals with multiple sclerosis and 502 teaching students in a program for a basic qualification certificate in physical education, Manuscript C cross-validates and extends these model variants to a ten-factor measurement solution. Second-order analysis and multidimensional scaling techniques demonstrated that the ten specified factors can be statistically bundled into three theory-conform second-order factors (movement competence, control competence, and self-regulation competence). Although the analyses comprised a total of 2,063 participants, cross-validations and more representative samples are required to put the assessment instrument on a stronger empirical footing. Nevertheless, the validations justify the use of the instrument with the included samples. Manuscript D examines the relevance of the three PAHCO sub-competences in 475 persons with multiple sclerosis. The path analyses in the multivariate case indicated that only self-regulation competence was significantly associated with the self-reported amount of physical activity, whereas movement competence (which was closely linked to disease severity) and control competence were not. However, control competence has shown an independent, theory-confirm relationship with individuals’ subjective health, going beyond the mere volume of physical activity. Manuscript E explores the usual physical activity behavior of apprentices in automotive mechatronics and nursing care as a first step. The accelerometer study with 55 apprentices from both sectors recorded considerable values, suggesting that mere volume is not an issue in this target group. In line with this result, an analysis of the 745 apprentices demonstrated in the second step that the physical activity volume was not correlated with an individual’s work ability and health. However, the PAHCO indicators as person-related resources in dealing with physical activities were consistently related to the two outcomes. Finally, Manuscript F investigates the predictive quality of the five PAHCO indicators (measured at the end of an inpatient rehabilitation stay) for the physical activity behavior and quality of life of rehabilitants with COPD six weeks and six months after pulmonary rehabilitation. The longitudinal accelerometer study with 327 participants underlined the considerable diagnostic power of a six-minutes walking test, which is often used as a standard measure in pulmonary rehabilitation. Furthermore, the five PAHCO indicators only provided inconsistent evidence with respect to the additional explanatory power of the two outcome variables beyond the six-minutes walking test. In summary, the three analyses yielded important findings for the specific populations of persons with multiple sclerosis, apprentices in nursing care and automotive mechatronics as well as individuals with COPD. Future studies could apply different analytical approaches to gain further insights. For instance, it could be worth dissolving the multivariate strategy, in which PAHCO indicators are simultaneously regressed on important outcome variables by applying moderating or mediating effects instead. Furthermore, analyses between populations could be performed through secondary data use and data-set merging. The dissertation concludes with general perspectives and challenges related to PAHCO. For instance, it would be worth promoting discussions on potential PAHCO applications for the physical education context. It is argued that sport-pedagogical arguments could complement the health science perspective to underpin schools as relevant settings of application. Furthermore, the theoretical and empirical results accumulated so far should be increasingly transferred into interventional endeavors, including the development of intervention components, their implementation into practice, and their subsequent evaluation. It would also be essential from a theoretical perspective to map out the relevance of the environment and structure within the PAHCO model as its role has not yet been sufficiently elaborated. Therefore, the final section of this doctoral dissertation suggests six different positions regarding how researchers dealing with competences for physically active lifestyles could design the competence-environment relationship within their models. In any case, tackling any of these challenges would further nourish the quasi-paradigmatic research program on PAHCO initiated by this cumulative doctoral thesis. <